Tissue Engineering Using Ceramics and Polymers, Third Edition - Boccaccini, Aldo R.; Ma, Peter X.; Liverani, Liliana (Elsevier, 2021)
Tissue Engineering Using Ceramics and Polymers, Third Edition is a valuable reference tool for both academic researchers and scientists involved in biomaterials or tissue engineering, including the areas of bone and soft-tissue reconstruction, repair and organ regeneration. With its distinguished editors and international team of contributors, this book reviews the latest research and advances in this thriving area and how they can be used to develop treatments for disease states. New sections cover nanobiomaterials, drug delivery, advanced imaging and MRI for tissue engineering, and characterization of vascularized scaffolds. Technology and research in the field of tissue engineering has drastically increased within the last few years to the extent that almost every tissue and organ of the human body could potentially be regenerated with the aid of biomaterials. .
CRIS-Team Scopus Importer:2024-12-16